Regulation of HCN2 Current by PI3K/Akt Signaling - Lu, Zhongju; Wang, Hong Zhan; Gordon, Chris R.; Ballou, Lisa M.; Lin, Richard Z.; Cohen, Ira S. (Frontiers in Physiology, 2020)
Abstract It has long been known that heart rate is regulated by the autonomic nervous system. Recently, we demonstrated that the pacemaker current, If, is regulated by phosphoinositide 3-kinase (PI3K) signaling independently of the autonomic nervous system. Inhibition of PI3K in sinus node (SN) myocytes shifts the activation of If by almost 16 mV in the negative direction. If in the SN is predominantly mediated by two members of the HCN gene family, HCN4 and HCN1. Purkinje fibers also possess If and are an important secondary pacemaker in the heart. In contrast to the SN, they express HCN2 and HCN4, while ventricular myocytes, which do not normally pace, express HCN2 alone. In the current work, we investigated PI3K regulation of HCN2 expressed in HEK293 cells. Treatment with the PI3K inhibitor PI-103 caused a negative shift in the activation voltage and a dramatic reduction in the magnitude of the HCN2 current. Similar changes were also seen in cells treated with an inhibitor of the protein kinase Akt, a downstream effector of PI3K. The effects of PI-103 were reversed by perfusion of cells with phosphatidylinositol 3,4,5-trisphosphate (the second messenger produced by PI3K) or active Akt protein. We identified serine 861 in mouse HCN2 as a putative Akt phosphorylation site. Mutation of S861 to alanine mimicked the effects of Akt inhibition on voltage dependence and current magnitude. In addition, the Akt inhibitor had no effect on the mutant channel. These results suggest that Akt phosphorylation of mHCN2 S861 accounts for virtually all of the observed actions of PI3K signaling on the HCN2 current. Unexpectedly, Akt inhibition had no effect on If in SN myocytes. This result raises the possibility that diverse PI3K signaling pathways differentially regulate HCN-induced currents in different tissues, depending on the isoforms expressed.